KDIGO (Kidney Disease: Improving Global Outcomes) criteria as a predictor of hospital mortality in cirrhotic patients - Bıyık, Murat; Ataseven, Hüseyin; Bıyık, Zeynep; Asil, Mehmet; Çifçi, Sami; Sayın, Serhat; Tonbul, H. Zeki; Demir, Ali (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Acute kidney injury (AKI) is frequent in cirrhotic patients and is associated with a poor prognosis. Recently, the Kidney Disease: Improving Global Outcomes (KDIGO) organization recommended new criteria for the diagnosis and staging for AKI. The aim of this study was to evaluate the presence of AKI according to KDIGO criteria in cirrhotic patients admitted to the hospital and to determine its association with hospital mortality. Materials and Methods: This retrospective study included 277 cirrhotic patients admitted to the intensive care unit and gastroenterology service of a tertiary referral hospital from January 2008 to January 2012. AKI was diagnosed and classified according to the KDIGO criteria. Results: The overall incidence of AKI in cirrhotic patients was 39%, and the overall hospital mortality was 15.5%. Patients without AKI had a hospital mortality rate of 2.4%, whereas the mortality rate for patients with AKI was 36.1%. The peak AKI stage detected during hospitalization was stage 1 for 58 patients (53.7%), stage 2 for 20 patients (18.5%), and stage 3 for 30 patients (27.7%). Mortality was found to be associated with the presence, stage, and progression of AKI. Multivariate analysis showed that AKI was an independent factor significantly associated with mortality (odds ratio: 9.1; 95% confidence interval: 2.89–29.1; p<0.001). Conclusion: KDIGO criteria can be used to evaluate AKI in cirrhotic patients. The prevalence of AKI in patients with cirrhosis is high, and AKI is associated with mortality. If early preventive measures are taken, it may be possible to prevent AKI progression and thus mortality.